Megafauna Seed Dispersal in the Neotropics: A Meta-Analysis Shows No Genetic Signal of Loss of Long-Distance Seed Dispersal - Collevatti, Rosane G.; Lima, Jacqueline S.; Ballesteros-Mejia, Liliana (Frontiers in Genetics, 2019)
Restricted gene flow may lead to the loss of genetic diversity and higher genetic differentiation among populations, but the genetic consequences of megafauna extinction for plant populations still remains to be assessed. We performed a phylogenetic independent meta-analysis across 102 Neotropical plants to test the hypothesis that plant species with megafaunal seed dispersal syndrome have lower genetic diversity and higher genetic differentiation than those without it. We classified as megafauna dependent plant species those that potentially relied only on megafauna to seed dispersal, and as megafauna independent those that relied on megafauna and other seed dispersers. Our data comprised 98 studies using microsatellite markers. We found no statistical difference in genetic diversity and differentiation between plants with megafauna and non-megafauna seed dispersal syndrome, although statistical power to detect differences in genetic differentiation was low. Moreover, we found no statistical difference between megafauna dependent and megafauna independent plant species. We then used Generalized Linear Mixed Models and Phylogenetic Generalized Least Square Models to investigate the effects of megafaunal seed dispersal syndromes and reproductive traits on variation in genetic diversity and genetic differentiation. We found no effect of megafaunal syndrome, rather, reproductive traits such as pollination mode, and mating and breeding systems showed significant effects. Our findings show that the genetic studies of Neotropical plants performed so far show no difference in genetic diversity and differentiation in plants with megafaunal compared to those with non-megafaunal seed dispersal syndromes. Our results also provide evidence pointing out that plant species with megafaunal seed dispersal syndromes may have used different strategies to counterbalance the extinction of their mutualistic megafauna dispersers, such as the dispersal by extant mammals that may promote long-distance seed dispersal. Our results also reinforce the importance of pollination to long-distance gene flow in Neotropical plants.